(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Haemdynamic pressor response to airway instrumentation is a hazardous complication of general anaesthesia along with post-operative pain. Pregabalin is a gaba pentenoid which possesses antiallodynic, anticonvulsant and antihyperalgesic properties. Aim and Objective: The study aimed to evaluate the effects of oral preoperative pregabalin in attenuating haemodynamic response to laryngoscopy and intubation and inattenuating post-operative pain inpatients posted for elective surgery under general anaesthesia. Methodology: This prospective randomized placebo controlled double blinded study was conducted on 50 patients of either sex by randomly allocating them in two groups (Group P & Group C). Result: There were 68% females and 32% males in group P while in group C there were 64% females and 36% males. In the groups receiving Pregabalin, the mean age was 34.60 ± 9.71 years, while in the placebo group it was 34.60 ± 9.20 years. Patients pre-medicated with pregabalin had an attenuated hypertensive response to laryngoscopy and intubation as compared to the placebo. VAS score was lower in the 2nd hr after the surgery in the pregabalin premedicated group that the placebo group. Conclusion: Consequently, it can be said that pregabalin is effective in reducing post-operative pain, the hypertensive response, and has effective analgesic characteristics. It is also a relatively safe medication with few side effects.